2000
DOI: 10.1590/s1517-74912000000100002
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors of Actinobacillus actinomycetemcomitans: other putative factors

Abstract: Actinobacillus actinomycetemcomitans is implicated as the causative agent of localized juvenile periodontitis. This organism possesses a large number of virulence factors with a wide range of activities and also interfere with tissue repair. Fifty isolates of A. actinomycetemcomitans from 20 periodontal patients were examined to evaluate other putative virulence factors. In this study, the capsule, DNase, coagulase, fibrinolysin, proteolytic, haemolysin and bacteriocin production, haemagglutination, serum sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
3
5
0
1
Order By: Relevance
“…It is worth noting that there was a higher prevalence of A. actinomycetemcomitans than in the generalized form of the disease. This is consistent with the relevance that this microorganism has in localized cases of the disease (13)(14)(15) . Finally, the microorganisms P. gingivalis and T. forsythia had the lowest prevalence, being found in 40% of the patients studied (Chart 3).…”
Section: Localized Aggressive Periodontitissupporting
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that there was a higher prevalence of A. actinomycetemcomitans than in the generalized form of the disease. This is consistent with the relevance that this microorganism has in localized cases of the disease (13)(14)(15) . Finally, the microorganisms P. gingivalis and T. forsythia had the lowest prevalence, being found in 40% of the patients studied (Chart 3).…”
Section: Localized Aggressive Periodontitissupporting
confidence: 89%
“…Aggressive periodontitis is a disorder of multifactorial origin, such as host response, genetic factors and the subgingival microbiota (6,9,11) . Some of the bacterial pathogenic species that have been linked to the development of aggressive periodontitis are: Aggregatibacter actinomycetemcomitans (Aa) (2,12) and Porphyromonas gingivalis (Pg) (13) , the first being particularly important in the localized form (14)(15) and the second one in the generalized form (15)(16) , but another group of periodontopathogens, including Tannerella forsythia (Tf ), Prevotella intermedia (Pi) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and Fusobacterium nucleatum (Fn) (15) have been linked to it. Studies have been conducted in Uruguay using traditional bacterial identification methods, but so far, there are no studies concerning the levels of simultaneous occurrence of the periodontal pathogens mentioned above in cases of aggressive periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of virulence depends on several virulence factors (Price, 2008) which includes capsular polysaccharide (Taylor and Roberts, 2005;Lindberg et al, 1979), capsule, DNase, coagulase, fibrinolysin, proteolytic, haemolysin, bacteriocin production, haemagglutination, serum sensitivity, epithelial cells attachment, hydrophobicity (Avila-Campos et al, 2000), lipase, antiphagocytic factor, biofilm (Prasad et al, 2009), extracellular enzymes production, presence of surface layer, lysine decarboxylase production and pili, (Pin et al, 1997) etc. There are several in vivo and in vitro assays to determine these virulence factors (Calderone et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The proficiency of utilizing India ink depends on various factors such as origin of stain, staining techniques, need for good microscope and visual observation and inference. Price [11] and Avila-campos et al [12] has shown that the measure of virulence depends on many virulence determinants like haemolysin which is overly connected to the beta-haemolytic bacteria subjected to virulence test in this study.…”
Section: Microbialmentioning
confidence: 70%